Comparative Metabolic Responses Induced by Pyridine and Imidazole in Blakeslea trispora - Liu, Yang; Li, Xiang-yu; Lu, Shu-huan; Yu, Chao; Zhang, Yu-zhou; Wang, Zhi-ming; Yao, Jian-ming (Frontiers in Bioengineering and Biotechnology, 2019)
Lycopene cyclase need to be inhibited by the blockers like pyridine or imidazole in the lycopene biosynthesis of B.Trispora. This work investigated how pyridine and imidazole impacted the basal metabolism of B.Trispora, especially imidazole had been used as the industrial blocker, thus the results helped us understand how imidazole could affect the lycopene production and application, and wonder if pyridine could be another choice of blocker in industry. The samples of different fermentation modes were taken every 12 hours and detected by GC-MS, then the data of materials were typed into SPSS 16.0, and analyzed by the method of Principal Component Analysis (PCA). 38 intracellular meaningful metabolites were analyzed in the lycopene process with imidazole, while only 14 significant metabolites were identified in the pyridine process. It was found that amino acids, fatty acids, organic acids including phosphoric acid, carbon source and imidazole derivatives explained the most variance in imidazole fermentation, correspondingly, fatty acids, carbon source and pyridine derivatives played important roles in pyridine fermentation, and above all, the residual of both blockers’ derivatives would bring the potential risks on applications of lycopene products. Predominantly, durene met 0.35µg/mg DCW with imidazole and piperidine formaldehyde attained 0.24µg/mg DCW with pyridine after the end of lycopene fermentations.